Modified workflow scheduling using hybrid PSO-GA algorithm in cloud computing - Oke, Omotayo Patrick (2019)
Cloud computing environment offers customers with multiple on-demand services and resource sharing. Business processes are managed using cloud-based workflow technology, which is one of the difficulties of using resources efficiently owing to the inter-task dependencies. A Hybrid GA-PSO algorithm is suggested in this paper to effectively allocate duties. The goal of the Hybrid GA-PSO algorithm is to reduce the makespan and cost and balance the load of dependent tasks in cloud computing environments over the heterogonous resources. Results of the experiment show that the PSO-GA algorithm reduces the complete workflow execution time, Compared to GA, PSO and GA-PSO. It also decreases the cost of implementation. It also increases the workflow application's load balancing over accessible resources. Finally, the findings acquired also showed that the suggested algorithm converges more quickly and with greater performance than other algorithms to ideal alternatives.